Inside Front Cover: Construction of Tissue‐Level Cancer‐Vascular Model with High‐Precision Position Control via In Situ 3D Cell Printing (Small Methods 7/2021). Issue 7 (14th July 2021) - Kim, Byoung Soo; Cho, Won‐Woo; Gao, Ge; Ahn, Minjun; Kim, Jongmin; Cho, Dong‐Woo
Abstract : In article number 2100072, Dong‐Woo Cho and co‐workers use in situ 3D cell printing technology to directly print size‐tunable and position‐controllable 3D metastatic cancer spheroids within the supporting bath with a perfusable vascular endothelium system. The cancer‐vascular interactions are generated through controlling the distance between the cancer spheroids and the vascular channel.